2020
DOI: 10.21082/jpasca.v17n1.2020.1-14
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi Sifat Fisikokimia, Sensori, Dan Fungsional Nasi Instan Dari Beras Amilosa Rendah

Abstract: <p>Gaya hidup masyarakat di zaman modern dituntut untuk bergerak cepat termasuk dalam menyiapkan makanan. Oleh karena itu, perlu dicari alternatif proses untuk mempercepat pengolahan beras dengan tetap mempertahankan nilai gizinya. Beras amilosa rendah memerlukan waktu pemasakan yang cepat dengan tekstur yang pulen sehingga cocok digunakan sebagai bahan baku nasi instan. Tujuan dari penelitian ini adalah untuk mempelajari karakteristik fisikokimia, sensori, dan fungsionalnya nasi instan dari beras amilos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 14 publications
1
7
0
13
Order By: Relevance
“…In contrast, the lowest water content was observed in treatment F3 at about 10.52%. This is in line with the research conducted by [9] on instant rice which yielded water content of 12.39%. A study by [10], on instant multigrain dhokla mix, observed a drastic decrease in water content due to the dehydration process.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, the lowest water content was observed in treatment F3 at about 10.52%. This is in line with the research conducted by [9] on instant rice which yielded water content of 12.39%. A study by [10], on instant multigrain dhokla mix, observed a drastic decrease in water content due to the dehydration process.…”
Section: Resultssupporting
confidence: 91%
“…The highwater content can be attributed to the processing method [11]. This notion is supported by [9], which suggests that there is an interaction between temperature and time during the processing that can increase the percentage of water content in an instant food product. During the steaming process, gelatinization initiates as water permeates starch granules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk density is also influenced by the addition of soy lecithin which, according to Hartono et al, contains more than 90% fat, which has a lower density [47] resulting in a decrease in bulk density [47][48][49]. Generally, the water absorption capacity of a material is related to its bulk density value [41,45]. Low bulk density in analog rice indicates that the analog rice has high porosity [41,50].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The physical characteristics of instant Bose consisting of rehydration time, rehydration ratio, expansion volume and hardness were shown in the Table 1. The rehydration time is the time required for the product to re-absorb the water, so the homogenous texture is obtained [13]. It is the main parameter of a instant product.…”
Section: Physical Characteristicsmentioning
confidence: 99%